ALGUNOS ASPECTOS TAXONOMICOS DE TRIATOMA SPINOLAI PORTER (HEMIPTERA: TRIATOMINAE) - Frías L., Daniel; Martínez, H.; Wallace, A. (Acta Entomológica Chilena, 2022)
A morphological description of eggs, nymphs and adults of Tnatoma spinolai is offered in this paper. A detailed morphological descriptions of T. spinolai help to differenciate different populations of this species.